Desorption modeling of hydrophobic organic chemicals from plastic sheets using experimentally determined diffusion coefficients in plastics - Lee, Hwang; Byun, Da Eun; Kim, Ju Min; Kwon, Jung Hwan (Marine Pollution Bulletin, 2018)
To evaluate rate of migration from plastic debris, desorption of model hydrophobic organic chemicals (HOCs) from polyethylene (PE)/polypropylene (PP) films to water was measured using PE/PP films homogeneously loaded with the HOCs. The HOCs fractions remaining in the PE/PP films were compared with those predicted using a model characterized by the mass transfer Biot number. The experimental data agreed with the model simulation, indicating that HOCs desorption from plastic particles can generally be described by the model. For hexachlorocyclohexanes with lower plastic-water partition coefficients, desorption was dominated by diffusion in the plastic film, whereas desorption of chlorinated benzenes with higher partition coefficients was determined by diffusion in the aqueous boundary layer. Evaluation of the fraction of HOCs remaining in plastic films with respect to film thickness and desorption time showed that the partition coefficient between plastic and water is the most important parameter influencing the desorption half-life.
Keywords: Bioavailability; Biot number; Chlorinated benzenes; Desorption models; Hexachlorocyclohexanes; Hydrophobic organic chemicals; Model simulation; Partition coefficient; Diffusion; Hydrophobic and Hydrophilic Interactions; Models, Chemical; Organic Chemicals; Plastics; Polyethylene; Polypropylenes; Risk Assessment; Waste Products; Water; Water Pollutants, Chemical; Bioavailability; Biot number; Diffusion coefficient; Partition coefficient; Polyethylene; Polypropylene